Characterizing BDS signal‐in‐space performance from integrity perspective. Issue 1 (25th January 2021) - Wang, Shizhuang; Zhai, Yawei; Zhan, Xingqun
Abstract: The full deployment of China's BeiDou navigation satellite system (BDS) was finalized in June 2020. To support safety‐critical applications, the system must provide assured signal‐in‐space (SIS) performance. As one of the key steps forward for BDS, this paper characterizes the SIS range errors (SISREs) for both the regional (BDS‐2) and the global (BDS‐3) systems from the integrity perspective. Following the safety standards in aviation, a data‐driven SISRE evaluation scheme is presented in this work. This scheme evaluates the overbounding user range accuracy (URA) and the prior fault probability to respectively capture the nominal and anomalous SIS behaviors. By processing the 4.5‐year ephemerides starting from 2016 for BDS‐2 and the recent 1.5‐year data from 2019 for BDS‐3, we preliminarily provide an overall picture of the BDS SIS characteristics and reveal the significant performance variation among different satellites.